The role of graphical calculator in developing mathematical argumentation - Magalhães, Maria da Graça (2012)
This paper discusses the role graphic calculators can play in the development of mathematical argumentation in the context of mathematics classroom, either in small or big groups. Acting as a researcher, the teacher designed a research task on rational functions and monitored its application in a 11th grade class. The proposed task was first discussed in small group and later with the whole class. Finally each student prepared an individual report. A qualitative and descriptive research methodology was adopted. Along this experiment the role of graphic calculators was crucial, helping students to understand the proposed task as well as in validating or rejecting previous conjectures, constructing and visualizing graphs of different functions, formulating proof attempts, and therefore contributing to the development of mathematical argumentation.